2022
DOI: 10.1021/acsomega.2c05363
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Hypoglycemic Effects of a Polyherbal Extract on Alloxanized Diabetic Rats

Abstract: The current study investigates the antioxidant, antidiabetic, hepatoprotective, and nephroprotective potentials of a polyherbal mixture containing the methanolic extracts of seeds from Nigella sativa, Cicer arietinum, Silybum marianum, and Citrullus colocynthis and the rhizome of Zingiber officinale. The polyherbal extract (PHE) showed significant total phenolic contents (187.17 GAE/g), ferric reducing power (28%), and radical-scavenging activity (86.16%). The PHE also showed a substantial hypoglycemic effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A variety of medications such as biguanides, sulfonylureas, thiazolidinediones, alpha-glucosidase inhibitors, etc., are available to manage diabetes and its associated abnormalities. However, the rate of mortality is still high due to the substantial side effects exhibited by such synthetic antidiabetic drugs . In 2021, 537 million individuals worldwide (diagnosed or undiagnosed) were estimated to have diabetes, and by 2045, that number is expected to rise by 46% to 784 million. , It is also reported that “The International Diabetes Foundation” (IDF) estimates that 10.5% of adults worldwide have diabetes and that number is expected to rise to 12.2% by 2045 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of medications such as biguanides, sulfonylureas, thiazolidinediones, alpha-glucosidase inhibitors, etc., are available to manage diabetes and its associated abnormalities. However, the rate of mortality is still high due to the substantial side effects exhibited by such synthetic antidiabetic drugs . In 2021, 537 million individuals worldwide (diagnosed or undiagnosed) were estimated to have diabetes, and by 2045, that number is expected to rise by 46% to 784 million. , It is also reported that “The International Diabetes Foundation” (IDF) estimates that 10.5% of adults worldwide have diabetes and that number is expected to rise to 12.2% by 2045 …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have been looking into medicinal flora to find out the most effective herbal formulations containing potent medicinal plants against diabetes . The safety and efficacy of herbal medications for the treatment of diabetes have been proven in the past studies. , The antihyperglycemic properties of such medicinal plants might be linked to the presence of phytochemicals such as flavonoids, terpenoids, alkaloids, glycosides, and carotenoids, which are scientifically validated for producing antidiabetic effects either by enhancing insulin secretion from pancreas or lowering insulin resistance …”
Section: Introductionmentioning
confidence: 99%